Space as place: mapping patterns of social life in public spaces - Guerreiro, M. R. (2017)
One of the most fascinating aspects in the study of urban spaces is the interaction of people – with the physical environment as well as with other people. Urban spaces comprise not only the physical aspects, like the form of buildings, the streets, etc., but also the people who live in them. This paper is about the understanding of the informal process which creates life in public spaces. How space configure people behavior? And how people behavior configure space? Is that space layout performative of life in public space and vice versa? Why some places work and others don’t? What are the evidences of the relationships between spatial patterns, life patterns and social patterns? Can we measure it, simulate it and use it in design? We will examine spatial and social patterns in small urban spaces in Lisbon. Through descriptive analyses and quantification, it would be discussed how space layout can contribute to the urban life. The research combines configuracional analysis with findings from observation in order to understand how physical structures influence human behavior. Space Syntax techniques will be used to describe and analyze spatial configurations in relation to social patterns, (Hillier and Hanson, 1984). The model involves a nonmetric understanding of space and suggests that the presence of pedestrian in a network can be explained by topology. At the same time, direct observation of pedestrian behavior was attempted to quantifiably isolate what elements of the space made it effective or, conversely, ineffective (Whyte, 1980).